Action in the Business Realm: Increasing Students' Entrepreneurial Spirit Through Production Unit-Based Teaching Factory Learning - Puspita, Wahyu Nia; Huong, Do Thuy (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The aim of this research is to determine students' entrepreneurial spirit through production unit-based teaching factory learning. Methodology: The type of research used in this research is quantitative with a quasi-experimental type. The number of samples taken was 60 students consisting of 30 students in class VIII A and 30 students in class VIII B. The data collection technique used included distributing questionnaires. The data analysis technique used in this research is comparative analysis or T-test between class data that implements production unit-based Teaching Factory learning and those that do not. Main Findings: Based on the results of the T-test carried out, it was found that there was a difference in entrepreneurial spirit between the group who took part in learning at the teaching factory and the group who did not take part. Novelty/Originality of this study: The novelty of this research is that it explores the transformative potential of production unit-based Teaching Factory learning in fostering a dynamic entrepreneurial spirit among students in the business realm.